Conditioned Brownian motion in planar domains - Burdzy, Krzysztof; Bass, Richard F. (Springer-Verlag GmbH, 1995)
We give an upper bound for the Green functions of conditioned Brownian motion in planar domains. A corollary is the conditional gauge theorem in bounded planar domains.
Conditioned Brownian motion
Keywords: conditional gauge; Green function; planar domain; capacity; conditioned Brownian; h–processes